Long Form Improvisation and American Comedy The Harold - Fotis, M. (Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Long form scenic improv began with the Harold. The comic philosophy of this form started an era of comedy marked by support, trust, and collaboration. This book tells of the Harold, beginning with the development of improv theatre, through the tensions and evolutions that led to its creation at iO, and to its use in contemporary filmmaking.